2018
DOI: 10.1071/fp17326
|View full text |Cite
|
Sign up to set email alerts
|

A study of transcriptome in leaf rust infected bread wheat involving seedling resistance gene Lr28

Abstract: Leaf rust disease causes severe yield losses in wheat throughout the world. During the present study, high-throughput RNA-Seq analysis was used to gain insights into the role of Lr28 gene in imparting seedling leaf rust resistance in wheat. Differential expression analysis was conducted using a pair of near-isogenic lines (NILs) (HD 2329 and HD 2329 + Lr28) at early (0 h before inoculation (hbi), 24 and 48 h after inoculation (hai)) and late stages (72, 96 and 168 hai) after inoculation with a virulent pathoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 102 publications
5
20
1
Order By: Relevance
“…sugar efflux transporters, DnaJ domain belonging to heat shock protein family (Bekh-Ochir et al 2013), a protein kinase domain, a NB-ARC domain and a cation/calcium exchanger. Such genes show an increased expression during defense reactions in wheat-leaf rust (Sharma et al 2018) and wheat-stripe rust interactions (Wang et al 2020) and as response to environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…sugar efflux transporters, DnaJ domain belonging to heat shock protein family (Bekh-Ochir et al 2013), a protein kinase domain, a NB-ARC domain and a cation/calcium exchanger. Such genes show an increased expression during defense reactions in wheat-leaf rust (Sharma et al 2018) and wheat-stripe rust interactions (Wang et al 2020) and as response to environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…A number of expression studies for wheat-rust pathosystem in the past suggested that the host rapidly and precisely re-program a large number of downstream signalling and defense genes for providing partial durable resistance against a broad range of fungal pathogens ,9,10,11,12,13 . This reprogramming may also involve epigenetic modi cations as shown in our own studies involving epigenetic modi cations (methylation, chromatin modi cation and ncRNA) of some downstream defense genes involved in leaf rust resistance mediated by race-speci c gene Lr28 and APR gene Lr48 12,13,14,15,16 . Among epigenetic modi cations, DNA methylation has received maximum attention, and has been shown to be involved in regulation of expression of genes involved in a variety of cellular processes, which control development and stress responses 18 .…”
Section: Introductionmentioning
confidence: 78%
“…RNA‐Seq has been widely used to deeply explore DEGs among the plants with different phenotypes (Hao et al., 2016; Powell et al., 2017; Sharma et al., 2018). In this study, the susceptible wheat, ‘Jing411’, and disease‐resistant NIL, ‘BJ‐1’, were cultured until the first leaf was fully unfolded.…”
Section: Methodsmentioning
confidence: 99%